Fundamental Frequencies of Elliptical Plates using Static Deflections - Altekin, Murat (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
Fundamental frequencies of solid and annular elliptical plates were approximated using the static deflections by means of finite element method (FEM) without computing the eigenvalues. The problem was formulated within the framework of the first order shear deformation theory (FSDT). The effects of (i) the inner and outer boundary conditions, (ii) the size of the perforation, (iii) the aspect ratio, and (iv) the thickness of the plate on the performance of the method were examined via a large number of numerical simulations. Convergence study was performed through h-refinement. Accuracy of the results was validated through comparison studies. The results reveal that the application of Morley's formula which does not require eigenvalue analysis approximates the fundamental frequency with finer mesh compared to the eigenvalue analysis. The method can be considered as a practical technique to approximate the fundamental frequency. However, the boundary conditions have dominant role on the accuracy of the solution particularly when the plate is perforated.
Keywords: Vibration; fundamental frequency; static deflection; plate; finite element; FREE-VIBRATION ANALYSIS; SHEAR DEFORMATION-THEORY; CHARACTERISTIC ORTHOGONAL POLYNOMIALS; FINITE-ELEMENT; TRANSVERSE VIBRATION; NATURAL FREQUENCIES; COMPOSITE PLATES; EDGE; Engineering